Ritual Merenden Tedong sebagai Penyelesaian Konflik Masyarakat Mamasa - Stepanus Stepanus; Izak Lattu; Tony Tampake (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
The Merenden Tedong ritual is performed by the Toraja Mamasa tribe in Mamasa Regency, West Sulawesi up to now. This study aims to describe the implementation of the Merenden Tedong ritual of the Mamasa community, and then examine the spiritual values contained therein as a solution to community conflict. The motive for doing this research is the threat of social conflict in the community that can cause social disharmony. The method used in this research is qualitative with a descriptive approach. Data obtained through the method of observation, interviews, and analysis. Interviews were conducted with traditional leaders, community leaders, village government and Merenden Tedong ritual practitioners. This research resulted in the following findings: the implementation of the Merenden Tedong ritual in Mamasa included stages: mediation, deliberation, shaking hands and praying, and eating together. While the spiritual values of the Merenden Tedong ritual include: Ma’bisara, Me’renden Tedong, Sitayuk sikamasei Sirande maya-maya, Mesa Kada di Patuo, patang Kada di Pomate and Sipapada. The spiritual values of the Merenden Tedong ritual are a solution to the Mamasa community's conflict and also serves to build peace.